THE ETHICAL TRANSFORMATION OF ‘UYAINAH BIN ḤIṢN: INSIGHTS FROM HADITH ANALYSIS - Amirudin, Helmi; Muhid, Muhid; Atim Muthoharoh, Isnaini Lu'lu' (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2025)
This study departs from the limitation of previous research, which predominantly examined ‘Uyainah bin Ḥiṣn al-Fazārī from historical and political perspectives, while the moral transformation dimension in the context of hadith has received little scholarly attention. It re-examines ‘Uyainah as a representative figure of Bedouin moral change through the prophetic guidance of the Prophet Muhammad SAW. Employing a qualitative approach that integrates textual and contextual analysis of narrations drawn from primary sources such as al-Isti‘āb fī Ma‘rifati al-Aṣḥāb, Ansāb al-Ashrāf, Faḍā’il al-Ṣaḥābah, Tārīkh al-Ṭabarī, and al-Iṣābah fī Tamyīz al-Ṣaḥābah, the study reveals that ‘Uyainah’s moral transformation occurred gradually through the internalization of compassion (raḥmah), justice, and prophetic exemplarity. The findings position hadith as the primary source of moral values in dialogue with John Locke’s theory of empiricism, where social experience functions as a medium for ethical formation. Accordingly, this research reaffirms the relevance of prophetic ethics for contemporary moral education, especially in the digital era that demands social ethics grounded in compassion, truthfulness and responsibility [Penelitian ini berangkat dari keterbatasan kajian sebelumnya yang umumnya menyoroti ‘Uyainah bin Ḥiṣn al-Fazārī dari sisi historis dan politik, sementara dimensi transformasi moralnya dalam perspektif hadis belum mendapatkan perhatian yang memadai. Kajian ini berupaya meninjau ulang figur ‘Uyainah sebagai representasi perubahan moral masyarakat Badui melalui bimbingan profetik Nabi Muhammad SAW. Dengan pendekatan kualitatif yang memadukan analisis tekstual dan kontekstual terhadap riwayat-riwayat dalam sumber primer seperti al-Isti‘āb fī Ma‘rifati al-Aṣḥāb, Ansāb al-Ashrāf, Faḍā’il al-Ṣaḥābah, Tārīkh al-Ṭabarī, dan al-Iṣābah fī Tamyīz al-Ṣaḥābah, penelitian ini menemukan bahwa transformasi moral ‘Uyainah berlangsung secara bertahap melalui internalisasi nilai rahmah, keadilan, dan keteladanan profetik. Temuan ini menempatkan hadis sebagai sumber utama nilai moral yang berdialog dengan teori empirisme John Locke, yang menyatakan bahwa pengalaman sosial menjadi medium pembentukan etika. Dengan demikian, studi ini menegaskan relevansi nilai-nilai hadis dalam rekonstruksi pendidikan moral kontemporer, termasuk di era digital yang menuntut etika sosial berbasis kasih sayang, kejujuran, dan tanggung jawab.]